2009
DOI: 10.1007/s00280-009-1093-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of necrosis and cell cycle arrest in murine cancer cell lines by Melaleuca alternifolia (tea tree) oil and terpinen-4-ol

Abstract: TTO and terpinen-4-ol had significant anti-proliferative activity against two tumour cell lines. Moreover, the identification of primary necrotic cell death and cell cycle arrest of the aggressive tumour cells highlights the potential anticancer activity of TTO and terpinen-4-ol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 42 publications
7
48
1
1
Order By: Relevance
“…Furthermore, bactericidal (Loughlin et al, 2008) and antifungal properties (Mondello et al, 2006) have also been found in terpinen-4-ol. Moreover, cytotoxicity of terpinen-4-ol on cancer cell lines, e.g., melanoma, has been reported (Calcabrini et al, 2004); which potently induces cell cycle arrest, apoptosis and necrotic cell death (Greay et al, 2010). There is no report of the clinically curative effect of terpinen-4-ol on cancer treatment, but terpinen-4-ol contained anti-inflammatory activity.…”
Section: Terpinen-4-ol Induces Autophagic and Apoptotic Cell Death Inmentioning
confidence: 97%
“…Furthermore, bactericidal (Loughlin et al, 2008) and antifungal properties (Mondello et al, 2006) have also been found in terpinen-4-ol. Moreover, cytotoxicity of terpinen-4-ol on cancer cell lines, e.g., melanoma, has been reported (Calcabrini et al, 2004); which potently induces cell cycle arrest, apoptosis and necrotic cell death (Greay et al, 2010). There is no report of the clinically curative effect of terpinen-4-ol on cancer treatment, but terpinen-4-ol contained anti-inflammatory activity.…”
Section: Terpinen-4-ol Induces Autophagic and Apoptotic Cell Death Inmentioning
confidence: 97%
“…Furthermore, it can impair the growth of human M14 melanoma cells (Calcabrini et al, 2004) as well as induces necrotic cell death coupled with apoptotic cell death and arrests cell cycle at G1 stage in mouse malignant mesothelioma AE17 and murine melanoma B16-F10 cells (Greay et al, 2010). Further studies of potential anti-cancer drugs with a variety of cell lines are necessary, because there are high variability responses in different cancer cells following treatment with cytotoxic agents.…”
Section: Induction Of Intrinsic and Extrinsic Apoptosis Pathways In Tmentioning
confidence: 99%
“…131,132 p53 is also involved in the regulation of necrosis. [133][134][135][136] The functional and structural interactions between Beclin-1 and the antiapoptotic proteins Bcl-2 and Bcl-xL participate to some degree in the cross-linking of apoptosis, autophagy, and necroptosis. 98,106,137,138 Collectively, studies have indicated that apoptosis, autophagy, and necroptosis are independent but interconnected by similar pathways and share initiator or effector molecules.…”
mentioning
confidence: 99%